Secrecy outage analysis of energy harvesting two‐way relaying networks with friendly jammer. Issue 13 (1st August 2019) - Nguyen‐Huu, Phong; Ho‐Van, Khuong; Bao, Vo Nguyen Quoc
Abstract : This study investigates two‐way relaying where an energy harvesting capable relay exchanges information between two sources. Legitimate information is wire‐tapped by an eavesdropper. To intercept wire‐tapping, this study exploits a friendly jammer. Secrecy outage analysis of the energy harvesting two‐way relaying network with the friendly jammer over Rayleigh fading channels is first proposed in terms of individual secrecy outage probabilities and then validated by computer simulations. Various results demonstrate the efficacy of the jammer in preventing the eavesdropper from stealing the source information and significant impacts of relay location, jammer location, jammer's transmit power, energy conversion efficiency, time switching ratio on the security performance.